2015
DOI: 10.1017/s0149767715000212
|View full text |Cite
|
Sign up to set email alerts
|

A Kinesthetic Mode of Attention in Contemporary Dance Practice

Abstract: In this article, original interview material, existing published accounts, and the author's own experience as a contemporary dancer are put in conversation to explicitly address a particular kinesthetic awareness, sensitivity, and curiosity valued and employed by a group of dancers in the practice of contemporary dance, which is referred to as a kinesthetic mode of attention. The research informing this article uses a phenomenological and sociological approach and discusses, in detail, what this mode of attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…In other words, we should also consider an improvisational aspect more specifically related to the way the dancers engage in kinesthetic explorations of their bodies while dancing. As has been highlighted by several dance researchers, despite steps and movement patterns being well-known, the body never feels the same when dancing choreographed steps (Purser 2017;Ravn 2017;Ehrenberg 2015). For example, one of the ballet dancers at the Royal Danish Ballet emphasized that when taking daily classes, as well as preparing himself for performances, he engages in a continuous exploration of the intertwinement between the look and the sensation of his movement in order to continuously develop his technique and to perform according to the balletic ideal.…”
Section: To Think Of Any Dance As Improvisedmentioning
confidence: 99%
“…In other words, we should also consider an improvisational aspect more specifically related to the way the dancers engage in kinesthetic explorations of their bodies while dancing. As has been highlighted by several dance researchers, despite steps and movement patterns being well-known, the body never feels the same when dancing choreographed steps (Purser 2017;Ravn 2017;Ehrenberg 2015). For example, one of the ballet dancers at the Royal Danish Ballet emphasized that when taking daily classes, as well as preparing himself for performances, he engages in a continuous exploration of the intertwinement between the look and the sensation of his movement in order to continuously develop his technique and to perform according to the balletic ideal.…”
Section: To Think Of Any Dance As Improvisedmentioning
confidence: 99%
“…Based on the study's specific objectives and literature review, the relevant topics were identified from which the questions were elaborated to ensure the credibility of what is being investigated (Roller & Lavrakas, 2015). Qualitative studies that were consulted, showed a focus on the dancer's moving experiences as a central point for exploring different topics, due to in-depth interviews to dancers: Ehrenberg (2015); Legrand and Ravn (2009); Hanley (2004); Long (2002); Lussier-Ley (2013); Potter (2008); Ravn and Hansen (2012); Rouhiainen (2003); Wilson (2009). Most of these studies don't present the interview guide, and some of them include the analysed issues and data discussion as a narrative.…”
Section: Design Of the Studymentioning
confidence: 99%
“…Bodies are an essential, ever present aspect of the self. Michel Foucault argues that the body is marked by social norms (Ehrenberg 2015). The physical nature of culture means that our bodies are essential to how we understand, comprehend, and form meaning (Assaf 2013).…”
Section: The Body Spongementioning
confidence: 99%
“…Affect is continuously present in the body and experience; it is inseparable from perception. Leading dance philosopher and phenomenologist Shantel Erhenberg postulates that to access this noncerebral, kinesthetic intelligence and intuit others' emotional states of being, one must expose the proprioceptive, sensuous sense of an embodied self (Ehrenberg 2015). An example of this can be found in Assaf's research (2013).…”
Section: The Body Spongementioning
confidence: 99%